2018
DOI: 10.21037/jtd.2018.03.184
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adjuvant chemotherapy for completely resected stage IB non-small cell lung cancer: a retrospective study

Abstract: Background: Lung cancer is being increasingly detected in the early stages, highlighting the importance of lung cancer screening. However, there is no consensus on the post-operative management of stage IB nonsmall cell lung cancer (NSCLC). Therefore, this study aimed to identify the predictive factors for prognosis of stage IB NSCLC and determine the efficacy of adjuvant chemotherapy on recurrence and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 30 publications
3
25
0
2
Order By: Relevance
“…The occurrence and development of NSCLC is complex, and decisions regarding the administration of adjuvant therapy for stage IB NSCLC patients remains controversial. Some research studies have suggested that patients with stage IB NSCLC could benefit from adjuvant therapy (16)(17)(18), while other studies have reported no effects of adjuvant chemotherapy on patients (9,11,12,(19)(20)(21). Studies that have shown the benefit of adjuvant chemotherapy in stage IB patients tend to recommend adjuvant therapy for patients with tumor size ≥4 cm (7,8,12,22,23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence and development of NSCLC is complex, and decisions regarding the administration of adjuvant therapy for stage IB NSCLC patients remains controversial. Some research studies have suggested that patients with stage IB NSCLC could benefit from adjuvant therapy (16)(17)(18), while other studies have reported no effects of adjuvant chemotherapy on patients (9,11,12,(19)(20)(21). Studies that have shown the benefit of adjuvant chemotherapy in stage IB patients tend to recommend adjuvant therapy for patients with tumor size ≥4 cm (7,8,12,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above results, some researchers hoped to provide information regarding postoperative treatment decisions by studying the prognosis of early-stage patients. Factors such as age, pathological type, LINE-1 hypomethylation, individualized immune prognostic signature, quality measures, tumor size, preoperative platelet-to-lymphocyte ratio and lymphocyte-tomonocyte ratio, and visceral pleural invasion, were found to influence the prognosis of early-stage patients (7,10,11,13,14,22,(26)(27)(28)(29)(30). However, the above mentioned studies were unable to individually predict the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Комбинированное лечение позволяет несколько улучшить выживаемость больных НМРЛ [1,3,6,7,12,15,16,17,18]. В то же время, у пациентов с ранними стадиями IА-IВ химиотерапия не только не улучшает, но даже может ухудшить отдаленные результаты [19,20,21]. Это только подтверждает тезис необходимости адекватного стадирования РЛ.…”
Section: актуальностьunclassified
“…Показаниями к назначению пред-и послеоперационной химиолучевой терапии в этой группе больных могут быть: N+, наличие опухолевых клеток по линии резекции бронха (R1), недостаточный отступ линии резекции бронха от края опухоли, низкая дифференцировка опухоли, другие показания требуют дальнейшего изучения и уточнения [19,20,21]. Список литературы…”
Section: оригинальные статьиunclassified